The Private Provision of Public Services: Evidence from Random Assignment in Medicaid - Agafiev Macambira, Danil; Geruso, Michael; Lollo, Anthony; Ndumele, Chima D.; Wallace, Jacob (American Economic Review, 2026)
This paper examines the effects of privatizing social health insurance in the United States. We study this question in the context of the Medicaid program, the largest health insurer in the US and the largest means-tested program in the nation -serving over 90 million low-income families and individuals with disabilities. Exploiting a natural experiment wherein nearly 100,000 Medicaid enrollees were randomly assigned between a state-administered fee-for-service system and private managed care, we find that spending was nearly 10% lower for enrollees assigned to managed care plans. These savings were concentrated in prescription drugs, where we show that prior authorization was the key mechanism plans used to reduce overuse and encourage substitution to lower-cost alternatives without reducing quality. This was distinct from the effects of privatization on medical benefits, where private plans lowered quality and abraded consumers without achieving savings. In contrast to what our findings imply for an efficient public-private division of services, Medicaid has historically favored the public provision of prescription drugs and private outsourcing of medical care.